2021
DOI: 10.2196/23916
|View full text |Cite
|
Sign up to set email alerts
|

An mHealth-Based Intervention for Adolescents With Type 1 Diabetes and Their Parents: Pilot Feasibility and Efficacy Single-Arm Study

Abstract: Background Type 1 diabetes (T1D) affects more than 165,000 individuals younger than 20 years in the United States of America. The transition from parent management to parent-child team management, with the child taking on increased levels of self-care, can be stressful and is associated with a deterioration in self-management behaviors. Therefore, a mobile app intervention, MyT1DHero, was designed to facilitate diabetes-specific positive parent-adolescent communication and improve diabetes-related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…For example, a randomized trial evaluating a diabetes management app for adolescents found that only 9% of participants had high engagement (using the app 3-7 days/week) [ 18 ], and a study evaluating a parent-developed app for diabetes management excluded 24% of participants from the analysis due to insufficient app use [ 19 ]. More recently, an app designed to facilitate positive parent-adolescent communication around diabetes management [ 8 , 20 ] found somewhat higher use; in a randomized pilot, the average app use was 58 out of 84 days for adolescents, but only 23 days for parents [ 8 ]. It is also unknown whether these apps would be acceptable for youth from minoritized racial and ethnic groups, as they were tested in predominantly non-Hispanic White youth or did not report on race or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a randomized trial evaluating a diabetes management app for adolescents found that only 9% of participants had high engagement (using the app 3-7 days/week) [ 18 ], and a study evaluating a parent-developed app for diabetes management excluded 24% of participants from the analysis due to insufficient app use [ 19 ]. More recently, an app designed to facilitate positive parent-adolescent communication around diabetes management [ 8 , 20 ] found somewhat higher use; in a randomized pilot, the average app use was 58 out of 84 days for adolescents, but only 23 days for parents [ 8 ]. It is also unknown whether these apps would be acceptable for youth from minoritized racial and ethnic groups, as they were tested in predominantly non-Hispanic White youth or did not report on race or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Several self-management games for T1D incorporate personal data, including real blood glucose measurement data [ 14 , 71 ]. Holtz et al [ 76 ] demonstrated that gamifying personal data is associated with improved glycemic control, quality of life, and diabetes behavior. Personal data enhances the educational effect by making the player understand how their decisions and actions affect the subsequent gameplay and heighten the player’s intrinsic motivation to play a self-management game, resulting in improved self-management [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noted in [10] that the transition from parental management of the course of treatment to management when a child takes on an increased level of self-help can be stressful. The MyT1DHero mobile app made it possible to facilitate positive communication between parents and children, increase adherence to diabetes treatment and quality of life.…”
Section: Mhealth For Children and Adolescents With T1 Diabetesmentioning
confidence: 99%